Multicultural awareness and citizenship identity formation in higher education: A phenomenological study of civic education students - Futika Permatasari; Fitri Mutmainnah; Harry Sugara; Eko Iswahyudi; Sunniyyatul Mustaghfiroh (Indonesian Journal of Educational Management and Leadership, 2026)
Purpose - This study aims to phenomenologically explore the experiences of Civic Education students regarding multicultural awareness in the university setting, as well as the complex processes involved in the formation of their civic identity. Method - This study uses a phenomenological approach with qualitative methods that aim to describe the construction of student identity and multicultural awareness. The type of phenomenology employed is social phenomenology based on Alfred Schutz’s perspective. This approach was chosen to examine how individuals subjectively construct meaning within the lifeworld. The primary focus of this study is on the aspect of intersubjectivity—specifically, how interpretations of citizenship identity and multicultural awareness are formed through interactions and typification schemes prevalent within specific social groups. The data collection methods in this study are observation and in-depth interviews. Findings - The results show that the construction of student citizenship identity is demonstrated through several stages, namely externalization, objectification, and internalization. Meanwhile, the multicultural awareness of students in the Civic Education Study Program, based on Robert Hanvey's cross-cultural awareness theory, has reached the stage of the intellectual & empathy stage. They are able to critically examine their own culture and view the world from others’ perspectives (cross-cultural empathy) as the essence of civic maturity. This understanding arises from habits and experiences when interacting with students from different cultures.